The effect of ultraviolet photofunctionalization on titanium implant surface and its related clinical performance - Zaheer, Naauman (2020)
Commercial titanium implants are highly reactive, and it eventually degrades with time due to accumulation of surface hydrocarbons from surrounding environment, which ultimately decreases the cellular attachment and bone formation on implant surface. The surface hydrocarbons can be reduced through ultraviolet (UV) irradiation of implants also known as photofunctionalization. The aim of the present study was that which wavelength of ultraviolet (UV) radiation is suitable to induce maximum positive effects on implant surface and compare it with non-UV irradiated implants. The main objective of this study was to assess the changes in pore diameter as well as changes in hydrocarbon levels on the surface of SLA coated titanium implants in laboratory study following UV irradiation with varying wavelengths. In the clinical part of the study, changes in marginal bone loss (MBL), bone density and implant stability in the alveolar bone surrounding the titanium implants were assessed and compared. The laboratory part of the study was conducted on nine Dio UFII implants with hybrid sandblasted and acid-etched (SLA) surface treatments, divided equally among three groups. Implants in control group A were not irradiated, while groups B and C samples were given UVA (382 nm, 25 mWcm2) and UVC (260 nm, 15 mWcm2) irradiation, respectively. Changes in pore diameter and the atomic ratio of carbon, titanium, oxygen and on implant surfaces were analysed and compared among the groups. In the clinical part of the study, sixty-six implants were placed in systemically healthy participants. Simplerandomization was employed to allocate patients into three groups. In group A (control group), patients received implants as it is without any intervention, while patients in group B (UVA group) and C (UVC group) received photofunctionalized implants. The MBL and bone density in the surrounding bone was evaluated through Cone Beam Computed Tomography (CBCT) at 8th and 26th week and comparisons were done among the three groups. It was observed in laboratory part of the study that UVC group showed more pronounced increase in pore diameter compared to UVA and control group. The surface carbon content was also considerably reduced, whereas percentages of titanium and oxygen were enhanced for group C compared to other groups. Meanwhile in the clinical part of the study, both UVA and UVC treated groups showed minimal MBL compared to control group. UVC group showed significant improvement in bone density between 8th and 26th week time. Implant stability was also evaluated at time of placement of implant fixture (day 0) and after 8th week before functional loading. Implants irradiated with UVA had relatively significant effect on ISQ level as compared to control and UVC group. In conclusion, UVC irradiation has the potential to increase the pore diameter and reduce the surface hydrocarbons, thus inducing more bone formation around the implant surfaces.